Semiotics of the advertising image of the needs of women between manifestations of the phenomenon and implicit analysis - محمد محفوظ الزهري (International Journal of Social Communication, 2020)
Semiotics of the advertising image of the needs of women between manifestations of the phenomenon and implicit analysis Research Summary: The visual image is composed of two basic speeches: the linguistic linguistic discourse, the visual and the visual discourse, and also includes the binary meaning and meaning. It also consists of three communicative elements: the first element is the sender and the second element is the ad image which is composed of the dial and the third element The researcher tried to analyze the advertising image related to the needs of women in the Arab websites through the identification of the tool for the analysis of semantic detection of the phenomenon and implicit analysis. The researcher raises the question about the semiotic dimensions of the advertisement image of the needs of women through the Arab websites on the level of the apparent and implicit researcher in the answer through the framework of the methodology of the study, which includes the problem of research, objectives and importance, and questions, data collection tools, And supported study of models of advertising images and mechanism of its semiotic analysis